Development of a computer vision system for electronic PCB component inspection - Nguyen, Viet Thang; Le , Thanh Tung; Mai , Van Nam (Journal of Technical Education Science, 2016)
The manufacturing process of Printed Circuit Board (PCB) nowsaday requires several high-tech procedures. Among them, components inspection on PCB usually requires high attention concentration and labor persistence. Solutions were suggested to solve this problem, among which computer vision emerged as one of the most suited with high speed and precise detection capacity, but usually high cost. This paper presents a solution to detect missing components on PCB using low cost camera and an appropriate algorithm that meets the requirements of the producer